9B.09: IDENTIFICATION OF MARKERS PREDICTIVE FOR MALIGNANT BEHAVIOR OF PHEOCHROMOCYTOMAS AND PARAGANGLIOMAS. (June 2015) - Evenepoel, L.; Van Nederveen, F.H.; Oudijk, L.; Papathomas, T.G.; Restuccia, D.F.; Belt, E.J.T.; Franssen, G.J.H.; Feelders, R.A.; Van Eeden, S.; Timmers, H.; De Herder, W.W.; Aydin, S.; et al.
Abstract : Objective: Pheochromocytomas and paragangliomas (PPGL) are relatively rare and mostly benign tumours. Approximately 10% of PPGL are malignant, as defined by the presence of metastases, i.e chromaffin tissue at a location that usually does not contain chromaffin cells. However, up to 35% of tumours in patients carrying an SDHB mutation appears to be malignant. Nowadays, no reliable marker allows to predict whether a PPGL is, or will become malignant. In addition, there are no curative treatments if metastases occur. The aim of the present study was to dentify genetic markers allowing to distinguish benign from malignant tumours. Design and method: An mRNA expression array was performed on benign and malignant PPGL. The genes showing a different expression between the benign and malignant tumours were selected to be confirmed and validated by qRT-PCR. Finally, the remaining genes were stained by immunohistochemistry on Tissue MicroArray including a large series of PPGL. Results: Forty benign and 12 malignant PPGL were investigated for differences in mRNA expression with Affymetrix arrays. Expression data were normalized according to Affymetrix recommendations. Then, using Pomelo II (http://pomelo2.bioinfo.cnio.es/ ), a Limma t-test was performed, to assess which genes were differentially expressed between benign and malignant PPGL. First, a non-clustered analysis was performed and 10 genes with a False Discovery Rate (FDR) below 0.05 and a relative overexpression ratio of at least 4 were found, including Interleukin 13 Receptor alpha 2 (IL13RA2) and Monooxygenase DBH-like 1 (MOXD1). Secondly, a supervised cluster analysis was performed (based on HIF target genes), resulting in 2 groups, which were both investigated for differences in mRNA expression between benign and malignant tumours. Five genes showed an FDR below 0.01 and were overexpressed in malignant tumours with a ratio higher than 4, including Contactin 4 (CNTN4), Iroquois Homeobox 3 (IRX3), and Sulfatase 2 (SULF2). These genes were further investigated using qRT-PCR, and immunohistochemistry on Tissue Micro Array including 91 benign and 12 malignant PPGL. Conclusions: Significant overexpression of Contactin 4 was shown in malignant compared to benign tumours, and may therefore contribute to distinguish malignant from benign PPGL.